Conceptual Analysis of Digiqual Model Based on 5s Theoretical Framework in Digital Libraries - Leila Sadat Siadati; Esmat Momeni; Mehdi Alipour Hafezi (بازیابی دانش و نظام‌های معنایی, 2017)
The purpose of the study is to orient the Digiqual model with the 5S theoretical framework in digital library concepts. The research type is practical and it was conducted using the analysis of qualitative content method. The validity of the research is a logical one which is based on personal subjective judgment. The reliability of the study is a type of credibility based on counseling the specialists in the field of digital libraries. In the digiqual model, content (information) and community (user) as two processes in digital libraries are related to technical environment and human/system interaction. Societies (actors) as a factor in dimensions of some ‘S’ concepts in digital libraries, including accessibility and pertinence of the digital object and also availability, effectiveness, extensibility, reusability and reliability of services, is appreciable with digiqual model. Scenario as a factor in dimensions of ‘S’ concepts in digital libraries including pertinence, and conservation of the digital object; availability, effectiveness, extensibility, reusability and reliability of services, is appreciable with digiqual model. Streams and structures as factors in dimensions of some ‘S’ concepts in digital libraries including accessibility, conservation, relevance, similarity, significance and timeliness of the digital objects; accuracy, completeness and conformance of metadata specification; completeness as a collection; completeness and consistency of the catalog; completeness and consistency in the repository; efficiency and effectiveness of services, is appreciable with digiqual model. Space as a factor doesn’t exist in any of the ‘S’ concept dimensions in digital libraries and it is not appreciable with digiqual model. Finally, the development of ‘S’ concepts in digiqual dimensions in order to integrate the quality of services is proposed.